2013
DOI: 10.1159/000351171
|View full text |Cite
|
Sign up to set email alerts
|

Oral Activated Charcoal Adsorbent (AST-120) Ameliorates Chronic Kidney Disease-Induced Intestinal Epithelial Barrier Disruption

Abstract: Background: Chronic kidney disease (CKD) impairs intestinal barrier function which by allowing influx of noxious products causes systemic inflammation. We have recently shown that intestinal barrier dysfunction in CKD is due to degradation of epithelial tight junction (TJ) which is, in part, mediated by influx of urea and its conversion to ammonia by microbial urease. We hypothesized that by adsorbing urea and urea-derived ammonia, oral activated charcoal (AST-120) may ameliorate CKD-induced intestinal epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 27 publications
5
71
0
Order By: Relevance
“…Treatment with dh404 reduced NFkB activity and inflammatory mediators and ameliorated depletion of the tight junction proteins. Earlier studies conducted by our group demonstrated the role of urea-derived ammonia and ammonium hydroxide generated by microbial urease in the gut lumen as a major cause of the disruption of intestinal epithelial tight junction [9], and its partial restoration by oral adsorbent [7]. The other potential mechanism known to cause tight junction breakdown is intestinal inflammation which leads to endocytosis of claudins and occludin as seen in inflammatory bowel diseases [12,40].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Treatment with dh404 reduced NFkB activity and inflammatory mediators and ameliorated depletion of the tight junction proteins. Earlier studies conducted by our group demonstrated the role of urea-derived ammonia and ammonium hydroxide generated by microbial urease in the gut lumen as a major cause of the disruption of intestinal epithelial tight junction [9], and its partial restoration by oral adsorbent [7]. The other potential mechanism known to cause tight junction breakdown is intestinal inflammation which leads to endocytosis of claudins and occludin as seen in inflammatory bowel diseases [12,40].…”
Section: Discussionmentioning
confidence: 92%
“…Almost 30 years ago, Vaziri et al [4] showed the presence of inflammation throughout the gastrointestinal tract (including gastritis, enteritis, and colitis) in a postmortem analysis of 78 hemodialysis patients. Recent studies by our group have demonstrated disruption of the epithelial tight junction throughout the gastrointestinal tract and its association with endotoxemia, local and systemic inflammation, and oxidative stress in animal models of CKD [5][6][7]. Subsequent in vitro studies revealed the role of urea and its conversion to ammonia and ammonium hydroxide as a main cause of the breakdown of the gut epithelial tight junction [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in vitro studies revealed significant depletion of the tight junction proteins and reduction of trans-epithelial electrical resistance in cultured human colonocytes incubated in media containing human uremic plasma [11]. Subsequent experiments have lead to the identification of ammonia, a product of microbial urease, as the principal mediator of uremia-induced intestinal barrier disruption [12,13].…”
Section: Ckd-induced Disruption Of Intestinal Epithelial Barriermentioning
confidence: 99%
“…This, in turn, leads to system inflammation and progressive damage to the renal function by allowing absorption of plasma endotoxin, IL-6, TNF-a, MCP-1, CINC-3, L-selectin, ICAM-1, and malondialdehyde into the circulatory system. 18 Experiments in a rat model of chronic kidney failure showed that urea directly enhances oxidative stress and insulin resistance, which play a central role in the pathogenesis of accelerated cardiovascular disease and numerous other CKD-associated complications. It was also observed that proteinuria was reduced and the decline in renal function was delayed by lowering the levels of blood urea in patients with CKD.…”
mentioning
confidence: 99%